Pelayanan Tour leader terhadap Kepuasan Jamaah: Studi Konsumen Biro Haji Umroh Hajar Aswad Mubaraq - Ali Rosidi; Arif Effendi (Pawarta: Journal of Communication and Da'wah, 2026)
Tour leader service plays a crucial role in Umrah travel by accompanying pilgrims throughout their pilgrimage journey. However, studies specifically examining the influence of tour leader service on pilgrim satisfaction remain limited. This study aims to examine the effect of tour leader service on Umrah pilgrim satisfaction at PT Hajar Aswad Mubaroq Surakarta, Indonesia. A quantitative correlational design was employed involving 90 respondents selected through simple random sampling. Data were collected using questionnaires and analyzed using descriptive statistics, Spearman rank correlation, and simple linear regression. The results reveal a very strong positive relationship between tour leader service and pilgrim satisfaction (rₛ = 0.805, p < .001). Regression analysis further indicates that tour leader service has a positive and significant effect on pilgrim satisfaction (B = 0.555, p < .001), explaining 63.8% of the variance in satisfaction. These findings highlight tour leader service as a key determinant of pilgrim satisfaction and emphasize the importance of strengthening service competence to improve the quality of Umrah travel services.